Modern approach to computer modeling of functional 3d objects in the professional training of future engineers and vocational education teachers - Derevyanchuk, Oleksandr; Lovska, Alyona; Ravlyuk, Vasyl; Dominikov, Mickolay; Derevianchuk, Yaroslav (Edelweiss Applied Science and Technology, 2024)
This article examines the features of computer modeling of functional 3D objects using the SolidWorks software suite, which is an integral component in the training of future engineers and vocational education teachers. The SolidWorks software suite provides tools not only for creating three-dimensional models but also for analyzing the mechanical properties of parts and visualizing the technical condition of objects. This enables future engineers and vocational education teachers to better understand the principles of designing and analyzing complex part structures. A step-by-step algorithm for computer modeling has been developed, from creating a basic sketch to completing a three-dimensional model of a functional object. It has been established that the computer modeling process allows for the selection of appropriate tools and commands for creating geometric transformations of objects and setting parameters. This ensures high accuracy in constructing a computer model according to its geometric parameters. It has been established that the modern approach to computer modeling in the educational process demonstrates the implementation of innovative technological solutions to improve the quality of training in higher education institutions. It has been determined that the proposed approach will not only help future engineers and vocational education teachers develop practical skills but also contribute to a deeper understanding of engineering concepts.